Sustainable bioenergy production - Singh, Veer Pratap (SCITUS Academics LLC, 2016)
Bioenergy is energy derived from biomass which includes biological material such as plants and animals, wood, waste, (hydrogen) gas, and alcohol fuels. In essence bioenergy is the utilisation of solar energy that has been bound up in biomass during the process of photosynthesis. Bioenergy is a renewable energy that can generate many additional benefits, the extent of which depends on a combination of factors including the types of feedstocks used, how they are produced and transported and the efficiency of the technologies deployed to convert them to bioenergy.